Building the future : innovation in design, materials, and construction : proceedings of the international seminar held by the Institution of Structural Engineers and the Building Research Establishment, and organized by the Institution of Structural Engineers Informal Study Group 'Model Analysis as a Design Tool', in collaboration with the British Cement Association and Taywood Engineering : Brighton, UK, April 19-21, 1993 - Garas, F. K.; Armer, G. S. T.; Clarke, J. L. (E & FN Spon, 1994)
This book forms the proceedings of the international seminar held by the Institution of Structural Engineers and the Building Research Establishment in Brighton in April 1993. It brings together contributions from 20 countries on recent innovations in building and construction. Developments in the design of structures, improvements in existing materials and the introduction of new materials have historically gone hand-in-hand. The limited range of materials available for construction at any one time dictates the practical range of structural form and performance. It follows that current design methods, materials and construction techniques may not be suitable to meet the demands of particular applications. The introduction of a new material or new practice may move the performance of the construction away from that which is reasonably well understood in the existing population of structures. By so doing, it may also lead to behavior which cannot be adequately predicted by the current design methods. Developments such as these therefore bring risks as well as benefits.; Innovations required to meet the clients' needs can also have a profound effect on the built environment It is important that any deleterious effects are limited. Undoubtedly all these risks can be most satisfactorily limited by sufficient high quality physical testing before any significant changes are introduced to construction. This book includes the role of physical tests in the development of design methods for new structural materials, new construction techniques and new forms of construction. It also includes papers demonstrating the practical application of these new methods in the construction of buildings, structures and civil engineering works.